Preservation of Indonesian in the border area of Aruk, Indonesia and Sarawak, Malaysia - Sulastriana, Elva; Herlina, Herlina; Hariadi, Try (citeus, 2022)
West Kalimantan is one of the provinces in Indonesia which has three border areas with Malaysia. Community interactions between countries that have been going on for centuries undeniably lead to language contact which results in people choosing local language so that communication can run effectively. The purpose of this study was to determine the variety of language used around the area, language attitudes, and the preservation of Indonesian in the border area of Aruk, Indonesia and Sarawak, Malaysia. Quantitative and qualitative methods were used in which the data were obtained through observation, questionnaires, and interviews with a total of 150 respondents. The results show that the variety of languages used by students, traders and government circles as the target speakers is Indonesian. Furthermore, the language serves as an instructional language in education settings, the language of communication, a unifying tool as well as the language of government administration, while the other local and regional languages are used in certain limited contexts. Regarding the attitudes, the people on the border of Aruk, Indonesia and Malaysia show a very positive attitude towards Indonesian. The defense strategy is carried out by students, traders, and the local government.